Excess mortality of 1 year in elderly hip fracture patients compared with the general population in Beijing, China. Issue 1 (December 2016) - Li, Shaoguang; Sun, Tiansheng; Liu, Zhi
Abstract Summary In a rapidly aging population, hip fractures have become an important public health issue in China. Presently, there is no study on the excess mortality of hip fractures in the mainland of China. This is the first study that presents excess mortality following hip fracture in Beijing, China. Purpose This study aims to assess the incidence and excess mortality of hip fracture patients aged 60 years or older from a municipal population database of Beijing. Methods We retrieved the Beijing municipal health insurance database of 2013 to identify beneficiaries who were at least 60 years older as total population of this age group and obtained the number of mortalities in a year. Among those people, subjects who have suffered hip fractures during the year were selected and a determination of the number of deaths in this period. Annual incidence of hip fracture, mortality, and excess mortalities was calculated and stratified by gender and age. Results During 2013, the annual incidence of elderly hip fracture in Beijing was 0.27 % and 1-year mortality was 23.44 %. Excess mortality odds ratios of males and females in three age groups were as follows: males, 2.23 (60–69 years old, 95% CI, 1.43–3.49), 2.99 (70–79 years old, 95% CI, 2.57–3.50), and 1.90 (≥80 years old, 95% CI, 1.64–2.22 ) and females, 3.12 (60–69 years old, 95% CI, 2.04–4.79), 1.93 (70-79 years old, 95% CI, 1.64–2.27), and 1.36 (≥80 years old, 95% CI, 1.21–1.55). Pulmonary complications were the leading cause of death, which accounts for 52.27 % of all. Conclusion Compared with the control population, hip fractures caused approximately twofold excess mortality rate during 1 year 2014 for elderly citizens in Beijing. Future studies are needed to explore the actual mechanism to design the most effective strategies for optimizing recovery from hip fracture.